Classification of Indian power coals using K-means clustering and self organizing map neural network - Pandit, Yogesh P.; Badhe, Yogesh P.; Sharma, B. K.; Tambe, Sanjeev S.; Kulkarni, Bhaskar D. (Fuel, 2011)
The present study reports results of the classification of Indian coals used in thermal power stations across India. For classifying these power coals a classical unsupervised clustering technique, namely ``K-Means Clustering'' and an artificial intelligence (AI) based nonlinear clustering formalism known as ``Self-Organizing Map (SOM)'' have been used for the first time. To conduct the said classification, five coal descriptor variables namely moisture, ash, volatile matter, carbon and gross calorific value (GCV) have been used. The classification results thereof indicate that Indian power coals from different geographical origins can be classified optimally into seven classes. It has also been found that the K-means and SOM based classification results exhibit similarity in close to 75% coal samples. Further, K-means and SOM based seven coal categories have been compared with as many grades of a commonly employed Useful Heat Value (UHV) based Indian non-coking coal grading system. Here, it was observed that a number of UHV-based grades exhibit similarity with the categories identified by the K-means and SOM methods. The classification of Indian power coals as provided here can be gainfully used in selecting application-specific coals as also in their grading and pricing. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Coal classification; Indian power coals; K-means clustering; Self-Organizing Map

Chemical looping reforming of ethanol for syngas generation: a theoretical investigation - Kale, Ganesh R.; Kulkarni, Bhaskar D.; Bharadwaj, K. V. (International Journal of Energy Research, 2013)
Chemical looping reforming (CLR) is a novel technology that can be used for reforming of cheaply available abundant biofuel like ethanol for the production of hydrogen/syngas for fuel cells. A systematic thermodynamic study for the CLR process using selected oxygen carriers was done to analyze the products and energy requirements of the CLR process in the temperature range of 5001200 degrees C at 1bar pressure for ethanol. The results showed favorable conditions for syngas manufacture from this process. Fe2O3 was found to be the best performing oxygen carrier followed by calcium and sodium sulfates, while Mn oxides were the least preferred oxygen carriers for CLR of ethanol process. The optimum process temperature was found to be 1000 degrees C. The actual CLR-ethanol process shows exothermicity against the theoretical endothermic partial oxidation of ethanol. The results obtained in this theoretical study can pave the way for experimental programs for syngas generation for SOFC-type fuel cells. Similar studies can be undertaken for other fuels for fuel processor development by CLR process. Copyright (c) 2012 John Wiley & Sons, Ltd.
Keywords: chemical looping reforming; ethanol to syngas; Fuel Processor; Gibbs minimization; oxygen carriers

Combined gasification of lignite coal: thermodynamic and application study - Kale, Ganesh R.; Kulkarni, Bhaskar D.; Chavan, Rank N. (Journal of the Taiwan Institute of Chemical Engineers, 2014)
Combined gasification (a combination of steam gasification and CO2 gasification) without air is an important process for research in coal gasification to reduce the steam generation energy in the gasification system and also to enhance the slow CO2 gasification reaction. A thermodynamic study involving the effect of temperature, pressure and feed CO2 and steam ratios in gasification of lignite coal was studied in this paper. The product generation trends of syngas and methane with carbon (in coal) conversion were studied in detail. The carbon (in lignite coal) was converted completely at a lower temperature than pure carbon in the combined gasification. Some applications of the gasifier product gas were also studied. Combined gasification offers great advantages to produce syngas of exact ratio in one step for use in petrochemical manufacture and fuel cell systems. The complete carbon (in coal) conversion occurred beyond the thermoneutral gasification temperature in the study. The combined gasification process was a useful way for CO2 utilization reducing the net CO2 emission to the atmosphere. (C) 2013 Taiwan Institute of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: CO2 utilization; Coal gasification; Coal to syngas; Combined gasification; Thermodynamic study

Characterization and valorization of biomass ashes - Trivedi, Nikhilesh S.; Mandavgane, Sachin A.; Mehetre, Sayaji; Kulkarni, Bhaskar D. (Environmental Science and Pollution Research, 2016)
In India, farming is the primary source of income for many families. Following each harvest, a huge amount of biomass is generated. These are generally discarded as "agrowaste," but recent reports have indicated several beneficial uses for these biomasses and their ashes. However, before the utilization of biomass ashes (BMAs), their chemical and physical properties need to be investigated (characterized) so as to utilize their potential benefit to the fullest. In this paper, eight different biomass ashes (soybean plant ash, mustard plant ash, maize ash, groundnut plant ash, cotton plant ash, wheat plant ash, pigeon peas ash, and groundnut shell ash) were characterized, and their chemical properties are discussed. Surface chemical composition analysis, proximate analysis, and ultimate analysis were performed on all BMA samples, and properties such as porosity, particle density, bulk density, point of zero charge, BET surface area, water-absorption capacity, and bulk parameters such as surface pH and surface charges were determined. BMAs were characterized by SEM and FTIR. The surface areas of biomass ashes vary from 1.9 to 46 m(2)/g, and point of zero charge for all BMAs exceed 9.8, which confirmed the alkaline nature of these samples. Based on the chemical composition, BMAs are categorized into four types (S, C, K, and CK), and their utilization is proposed based on the type. BMAs find applications in agriculture and construction industries; glass, rubber, and zeolite manufacturing; and in adsorption (as a source of silica/zeolites). The paper also discusses the research challenges and opportunities in utilization of BMAs.

Characterizing fruit and vegetable peels as bioadsorbents - Pathak, Pranav D.; Mandavgane, Sachin A.; Kulkarni, Bhaskar D. (Current Science, 2016)
Fruit and vegetable peel (FVP) wastes are a commonly generated organic waste from both households and food-processing industries. However, FVPs are low-cost lignocellulosic materials that have some potential for reutilization. For its particular reutilization, the characterization of FVP is essential. In this regard, the present study provides a detailed physico-chemical characterization of commonly used FVPs such as pomegranate, pineapple, watermelon, garlic, green pea and pigeon pea. The materials were characterized by SEM, FTIR and TGA/DTG. Various properties of these materials, such as porosity, particle density, bulk density, surface charges, point of zero charge, surface pH, water absorption capacity and BET surface area were determined. The BET surface area of FVP was found in the range 1.0-1.4 m(2)/g. Water absorption capacity was highest for watermelon peel (11.5 ml/g), while it was lowest for pigeon pea peel (5.5 ml/g). Point of zero charge and surface pH of all FVPs were in the acidic range 3-6. The surface of FVP was irregular and rough with some pores. Thermal analysis showed that FVPs are thermally stable below 150 degrees C. The results of this study provide an understanding of the properties of FVPs and suggest that the materials can be used as a low-cost adsorbent.
Keywords: Bioadsorbent; fruit and vegetable peels; organic waste; physico-chemical characterization

Comparative evaluation of packed-bed performance of biomass ashes as adsorbents for removal of diuron from aqueous solution - Deokar, Sunil K.; Mandavgane, Sachin A.; Kulkarni, Bhaskar D. (Desalination and Water Treatment, 2016)
The packed-bed performance of biomass ashes (BMA), namely rice husk ash (RHA) and bagasse fly ash (BFA), was investigated for adsorptive removal of diuron (herbicide) under dynamic conditions. The effects of influent concentration (10-30mg/L), flow rate (1-3mL/min), and bed height (3-11cm) were studied at 30 degrees C and results were analyzed using various packed-bed models. The saturation time and capacity of the BFA bed were found to be approximately 1.5 and 1.6 times higher due to higher BET surface area than that of RHA bed. However, the bed utilization of RHA was higher because of smaller mass transfer zone. At a constant influent concentration (20mg/L) and flow rate (1mL/min), the maximum volume of diuron treated was 1,325 and 1,685mL using RHA (bed height 10cm) and BFA (bed height 11cm), respectively. Among the packed-bed models applied, the BDST model revealed the inconsistent MTZ and complex mechanism involving more than one rate-controlling step for the adsorption of diuron on both ashes. The kinetics in the initial part of the breakthrough curve was governed by external mass transfer according to the Bohart-Adams and Wolborska models. Better agreements between experimental and predicted values of bed capacities for each ash and the higher bed capacity of BFA than RHA were demonstrated by the Thomas model. The Yoon-Nelson model was found to be superior for BFA rather than for RHA to estimate 50% saturation time. However, the deactivation kinetic model, previously discovered and applied only for gas-solid adsorption, was found to be the best for the diuron-BMA (liquid-solid) adsorption system in this study.